Revisiting the Falklands-Malvinas Question Transnational and Interdisciplinary Perspectives - Mira, Guillermo; Mira Delli-Zotti, Guillermo; Pedrosa, Fernando (University of London Press, 2021)
The conflict over possession of the Falklands-Malvinas Islands was waged in an area remote both geographically and geo-politically in an era of cold war and also of tensions within and between sovereign states of the supposed western bloc. It has been broadly perceived as an absurd confrontation, the echoes of which, despite the brevity of its duration, and some four decades on, resonate still not least in the lasting wounds that bear testimony yet to its underlying causes. This book probes the reasons behind the conflict's tragic occurrence and the processing of its consequences in and beyond the sovereign states that suffered and suffer still from the exacerbating of nationalist identities in the resolution of their differences and the consequent challenges to be addressed. Drawing on perspectives that bring together contributors from markedly differing backgrounds, whether national or disciplinary, this collection reinforces the spirit of critical questioning that historical and sociological research must ever value and pursue. Prejudices and preconceptions are acknowledged and confronted yet contextualised and revised through filters of new questions and answers which are not always anticipated or, for the stubbornly partisan, readily embraced.